Household income expectations: The role of shocks and aggregate conditions - Alessandro Bucciol; Joshy Z. Easaw; Serena Trucchi (Cardiff University, Cardiff Business School, 2024)
We conduct an empirical investigation to examine how income shocks and aggregate conditions influence income expectations, expectation uncertainty and expectation errors. We use data from a large longitudinal Dutch survey collecting detailed information on household income expectations. Our results show that income shocks, much more than aggregate conditions, induce a revision in income expectations across the entire spectrum of the income distribution. This expectation revision is consistent with an extrapolative behavior. We also observe that positive income shocks lead to an increase of expectation uncertainty. Our results partly confirm overreaction of respondents to income shocks, particularly for negative income shocks and high-income respondents. The above overall findings vary conditional on the position in the income distribution. This evidence may depend on different income processes and different degrees of awareness regarding the impact of income shocks and aggregate conditions.
Keywords: D84; G50; 330; ncome expectations; Expectation uncertainty; Expectation error; Income shocks; Aggregate conditions